Epikarst storage in a karst aquifer: a conceptual model based on isotopic data, Milandre test site, Switzerland - Perrin, Jérôme; Jeannin, Pierre-Yves; Zwahlen, François (My University, 2003)
The Milandre test site is a karst aquifer characterized by diffuse infiltration, a well developed conduit network, and several tributaries feeding an underground river. Field data include discharge rate measurements, stable isotopes, weekly rainfall and spring-water isotope sampling, and detailed isotope sampling during three flood events. Flood sampling was carried out at several tributaries corresponding to conduit flow, vadose flow and seepage flow. Weekly sampling showed a strong buffering of the rainfall isotopic signal at the spring. This attenuation suggests an important mixing reservoir in the system. Flood events showed highly peaking hydraulic responses but buffered rain isotope responses. These results indicate that the soil and epikarst sub-systems have an important storage capacity. A conceptual model of flow and transport in the soil and epikarst zone is proposed: Soil plays an important role in mixing due to the presence of capillary water storage. Consequently dampened concentrations reach the epikarst despite a rapid hydraulic response. The epikarst acts as the storage element and distributes water as either a base flow component or a quick flow component. When recharge exceeds a given threshold, excess infiltrated water bypasses the soil and epikarst and reaches the saturated zone as fresh flow. Based on this model, the significance of phreatic storage is thought to be limited, at least in Milandre test site. Hence the saturated zone is seen mainly as a transmissive zone through its well developed conduit network. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: karst hydrology; solute transport; water storage; stable isotopes; unsaturated zone; STABLE ISOTOPES; WATER; FLOW; TRANSPORT; SEEPAGE; SYSTEM; ZONE; CAVE; HYDROLOGY; TRACERS